Fundamental Shakespeare : new perspectives on gender, psychology and politics - Salami, Ali; Beyad, Maryam (Cambridge Scholars Publishing, 2016)
The contributions to this book examine various facets of the work of Shakespeare from an Eastern perspective. As such, Fundamental Shakespeare sheds fresh light on, and offers new insights to, a wide range of topics including politics, psychology and discourse. Divided into three separate categories, this volume brings to the fore long-standing, but under-explored areas of Shakespeare studies.